Mídia, opinião pública e segurança jurídica no processo penal : garantismo para todos ou direito penal do inimigo para alguns? - Lima, Igor Raphael Nascimento (2023)
The dissertation aims to analyze the participation of media and Public Opinion in Criminal Procedure, demonstrating how they affect the application of Law. Therefore, based on the hypothetical-deductive method, two initial premises were proposed and analyzed: external participation is positive because it democratizes the process and does not interfere with the enforcement of criminal and procedural rights and guarantees; or participation is negative, because it directs the judge to issue activist decisions that consolidate a treatment model that suppresses the rights and guarantees of the accused. For that, the study was divided into three chapters: the first demonstrates the trajectory of Criminal Law in individual’s search for legal security and a more humane application of the penalty, starting from the ancient to the modern, with emphasis, in this last moment, on the antagonistic theories of Criminal Guaranteeism, by Luigi Ferrajoli, and Criminal Law of Enemy, by Günther Jakobs; the second analyzes the consolidation of a penal system guaranteed by the 1988 Constitution and the participation of the Judiciary in the constitutional implementation, from which derive the phenomena of Judicialization of Politics and Judicial Activism; and the third, verifies the relationship between media, Public Opinion and criminal procedure, in order to identify the influence that is exercised in performance of the Judiciary when faced with crimes with greater repercussions. It was concluded that the mass media disseminate punitive conceptions in society, based on the propagation of fear and insecurity. In this scenario, news of crimes are transformed into spectacles and, in an appealing tone, the accused is presented as guilty, without any room for his presumption of innocence. The Criminal Procedure is then conceived as an instrument for fulfilling punitive expectations and, when the judge is contaminated by the unrestrained desire to do justice, it undermines his impartiality and tends to make activist decisions that, contrary to the law, suppress rights. and guarantees and give the accused treatment that is similar to what Jakobs proposes to the enemy. With the stain of the Rule of Law, there is the veiled institutionalization of a Criminal Law of Enemy.